2021
DOI: 10.1007/s10882-021-09800-1
|View full text |Cite
|
Sign up to set email alerts
|

“Tell Me About Your Child, The Relationship with Your Child and Your Parental Experiences”: A Qualitative Study of Spontaneous Speech Samples Among Parents Raising a Child with and without Autism Spectrum Disorder, Cerebral Palsy or Down Syndrome

Abstract: Ample quantitative studies have shown that parents raising children with neurodevelopmental disabilities are prone to experience more stress and challenges in their parenthood. Notwithstanding the strength of this line of research, qualitative studies are crucial to grasp the complex reality of these parenting experiences. This qualitative study adopted the Self-Determination Theory to analyze parents' described experiences, appraising both challenges and opportunities in parents' psychological need for autono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 83 publications
1
20
0
Order By: Relevance
“…Furthermore, for children with fragile X syndrome, parent EE profiles of increased warmth coupled with decreased criticism are associated with better behavioural outcomes (Greenberg et al, 2012). Research on EE in parents of children with Down syndrome is more limited but initial findings suggest a pattern of high parent warmth (De Clercq et al, 2022). Beck et al (2004)…”
Section: Expressed Emotion In Families Impacted By Intellectual Disab...mentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, for children with fragile X syndrome, parent EE profiles of increased warmth coupled with decreased criticism are associated with better behavioural outcomes (Greenberg et al, 2012). Research on EE in parents of children with Down syndrome is more limited but initial findings suggest a pattern of high parent warmth (De Clercq et al, 2022). Beck et al (2004)…”
Section: Expressed Emotion In Families Impacted By Intellectual Disab...mentioning
confidence: 99%
“…Furthermore, for children with fragile X syndrome, parent EE profiles of increased warmth coupled with decreased criticism are associated with better behavioural outcomes (Greenberg et al, 2012). Research on EE in parents of children with Down syndrome is more limited but initial findings suggest a pattern of high parent warmth (De Clercq et al, 2022). Beck et al (2004) found lower EE than expected in a sample of parents of children with ID and hypothesized that the high proportion of children with Down syndrome in their sample may have skewed their results due to the ‘Down syndrome advantage’ within intellectual disability populations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…x De Clercq, Prinzie, Swerts, et al, 2022 This qualitative study aims to provide a deeper understanding of the perspectives of parents raising an adolescent with ASD, CP, and DS and a reference group of parents raising a child without any known disability (i.e., reference group).…”
Section: Respondentsmentioning
confidence: 99%
“…Failure to adjust to the social world may lead students to increase the likelihood of suffering from various psycho-social problems (Lange & Couch, 2011;Saleem et al, 2014). Most typical difficulties encountered by university students are mood disruptions, problematic behavior, interpersonal problems, and deterioration of self-esteem (Chung et al, 2017;Matin & Khan, 2017) which are associated with numerous adverse outcomes including low self-esteem, loneliness, substance use and poor academic performance (De Clercq et al, 2022;New & Ghafar, 2016).…”
mentioning
confidence: 99%